The Role of Technology in Improving Early Childhood Social Skills - Suryaningsih Suryaningsih; Eny Nur Aisyah (Education and Sociedad Journal, 2025)
This study aims to analyze the role of technology in improving early childhood social skills in Early Childhood Education. This study departs from the increasing use of technology in early childhood education and the debate about its impact on children's social interactions. Although technology has great potential in supporting collaborative learning, its effectiveness in building children's social skills still needs further research. This study uses a qualitative approach with a descriptive research type, with data collection techniques carried out through interviews with teachers, parents, and children, as well as direct observation in the classroom and documentation related to the use of technology in learning. The results of the study indicate that the application of technology in collaborative learning can improve children's communication, cooperation, and social interaction skills. The findings also reveal that the role of parents and teachers is crucial in directing the use of technology to continue to support healthy social interactions. This study is expected to provide a deeper understanding of how technology can be optimized in early childhood education to strengthen their social skills.